Integration of large scale wind energy with electrical power system in China - Lu, Zongxiang, 1974-; Zhou, Shuangxi, 1941- (John Wiley & Sons, 2018)
An in-depth examination of large scale wind projects and electricity production in China -Presents the challenges of electrical power system planning, design, operation and control carried out by large scale wind power, from the Chinese perspective -Focuses on the integration issue of large scale wind power to the bulk power system, probing the interaction between wind power and bulk power systems -Wind power development is a burgeoning area of study in developing countries, with much interest in offshore wind farms and several big projects under development -English translation of the Chinese language original which won the "Fourth China Outstanding Publication Award nomination" in March 2013.
Keywords: Hybrid power systems -- China.; Wind power -- China.; elektronické knihy; electronic books